Performance evaluation of typical automatic technical safety barriers in chemical atmospheric storage tank areas - Tianyu Wang; Mingguang Zhang; Xueliang Tan (PLoS ONE, 2026)
Atmospheric storage tank farms in chemical industrial parks pose significant safety risks due to their complex layouts and the storage of flammable and explosive substances, which can trigger domino accidents. Automated safety barriers are widely applied, but their quantitative performance assessment remains a challenge in frameworks such as Accidental Risk Assessment Methodology for Industries (ARAMIS). To address this gap, this study proposes a quantitative model that evaluates safety barriers through the combined metrics of effectiveness and reliability. Water spray systems were selected as a representative barrier and analyzed using Pyrosim and ANSYS Workbench. The simulations revealed that tank failures mainly occur at the junction of the tank wall and roof as material properties degrade at elevated temperatures. Results showed that while water spray systems reduce thermal radiation damage, their protective effect decreases with increasing wind speed. Effectiveness was quantified through failure time extension and failure probability reduction, whereas reliability was evaluated via a Bayesian Network (BN) model. Integrating these factors produced a comprehensive performance index. Application of the model in a case study yielded a performance score of 0.752 for the water spray system, demonstrating both its protective capability and the practicality of the proposed method. Compared with the traditional ARAMIS framework, this approach offers improved precision and a more robust quantitative assessment for safety barrier performance in chemical storage tank areas.